2018
DOI: 10.4314/jfas.v9i6s.102
|View full text |Cite
|
Sign up to set email alerts
|

Nutritional supplement intake knowledge among university active graduates

Abstract: The purpose of this study is to examine the nutritional supplement intake knowledge among university athletes. Fifty-one university athletes volunteered to participate in this survey study.Results showed the nutritional supplement intake was significantly higher compared to the knowledge that they have about the supplements. Besides that, the performance was significantly greater compared to the supplement intake. To conclude, it is important for the coaches to educate their athletes on the importance and risk… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 3 publications
0
2
0
Order By: Relevance
“…From the results, it showed that these sports students interested in consuming DS even though they have less information on the importance of DS. In-class lectures and during participation in the sports are their sources of information towards DS (Mustafa, Awang, & Nadzalan, 2018). Nonetheless, previous studies reported that health care students lacked the knowledge regarding the use of DS when compared to working professionalsA past study in Poland explored DS consumption among the general public.…”
Section: Perceptions Of Knowledgementioning
confidence: 99%
“…From the results, it showed that these sports students interested in consuming DS even though they have less information on the importance of DS. In-class lectures and during participation in the sports are their sources of information towards DS (Mustafa, Awang, & Nadzalan, 2018). Nonetheless, previous studies reported that health care students lacked the knowledge regarding the use of DS when compared to working professionalsA past study in Poland explored DS consumption among the general public.…”
Section: Perceptions Of Knowledgementioning
confidence: 99%
“…The supplementation intake by athletes was often based on unfounded beliefs rather than the content itself (Garthe & Maughan, 2018). In the previous study by Mustafa et al, (2017), university athletes just consume supplements without knowing the importance of before training, after training, during, and after the game. Subgroups of university athletes had a higher risk to use supplements that may harm their health and eligibility (Sassone et al, 2019).…”
Section: Introductionmentioning
confidence: 99%